Starvation to Glucose Reprograms Development of Neurovascular Unit in Embryonic Retinal Cells - Özgümüs, Türküler; Sulaieva, Oksana; Jain, Ruchi; Artner, Isabella; Lyssenko, Valeriya (Frontiers in Cell and Developmental Biology, 2021)
Perinatal exposure to starvation is a risk factor for development of severe retinopathy in adult patients with diabetes. However, the underlying mechanisms are not completely understood. In the present study, we shed light on molecular consequences of exposure to short-time glucose starvation on the transcriptome profile of mouse embryonic retinal cells. We found a profound downregulation of genes regulating development of retinal neurons, which was accompanied by reduced expression of genes encoding for glycolytic enzymes and glutamatergic signaling. At the same time, glial and vascular markers were upregulated mimicking the diabetes-associated increase of angiogenesis – a hallmark of pathogenic features in diabetic retinopathy. Energy deprivation as a consequence of starvation to glucose seems to be compensated by upregulation of genes involved in fatty acid elongation. Results from the present study demonstrate that short-term glucose deprivation during early fetal life can have detrimental and lasting effects on gene expression in the retinal neurons, glial cells and vascular elements, and thus disrupting gene regulatory networks essential for the formation of the retinal neurovascular unit. Abnormal developmental programming during retinogenesis may serve as a trigger of reactive gliosis, accelerated neurodegeneration and increased vascularization, which may promote development of severe retinopathy in patients with diabetes later in life.